1989
DOI: 10.1016/s0006-3495(89)82684-0
|View full text |Cite
|
Sign up to set email alerts
|

Proton flux in large unilamellar vesicles in response to membrane potentials and pH gradients

Abstract: The transport of protons across liposomes composed of phosphatidylcholine in response to electrical potentials or pH gradients has been investigated. The results support three major conclusions. The first of these concerns the need for reliable measurements of electrical potentials and pH gradients. It is shown that the potential probe tetraphenylphosphonium and the pH probe methylamine provide accurate and self consistent measures of electrical potentials and pH gradients respectively in these systems. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…After the initial phase, an exponential decay phase then follows, where the pH i of the cells decreases towards pH ex (figure 4). The relatively good single exponential fit suggests that only passive diffusion controls the change in pH i after the start of the exponential decay [23,33]. As thermal deactivation of transporters and pumps in the cell membrane occurs, the cell will lose the ability to actively regulate the pH i .…”
Section: Discussionmentioning
confidence: 99%
“…After the initial phase, an exponential decay phase then follows, where the pH i of the cells decreases towards pH ex (figure 4). The relatively good single exponential fit suggests that only passive diffusion controls the change in pH i after the start of the exponential decay [23,33]. As thermal deactivation of transporters and pumps in the cell membrane occurs, the cell will lose the ability to actively regulate the pH i .…”
Section: Discussionmentioning
confidence: 99%
“…pH-partition hypothesis). However, recent studies suggest H + /OH permeability to be surprisingly high, as high as 10 -4 cm/s, greatly exceeding that of about 10 -12 cm/s for Na + [373][374][375][376][377][378][379][380][381]. Biegel and Gould [381] rapidly changed the pH ("acid pulse measurements") of a suspension of SUV (small unilamellar vesicles, soybean PC) from the equilibrated pH 8.2 to the external pH 6.65, and monitored the rate of influx of H + into the vesicles.…”
Section: Water Wires and H + /Oh -Currentsmentioning
confidence: 99%
“…Membrane potentials (negative inside) and transmembrane pH gradients (acidic inside) were assessed by measuring the transbilayer distribution of [3H]TPP+ and ['4C]MeAm employing the minicolumn separation method described above (Rottenberg, 1979;Hope et al, 1985;Redelmeier et al, 1989). [3H]TPP+ was added at 1 ,uCi/ml (corresponds to 0.026 nM) and ['4C]MeAm at 0.24 ,uCi/ml (5.8 ,uM) final concentrations to the vesicle suspensions in the presence or absence of peptide.…”
Section: Determination Of A*4 and Aphmentioning
confidence: 99%
“…The methylamine distribution was translated to a ApH value according to ApH = log ([MeAm]jj/[MeAm]O). Redelmeier et al (1989) have demonstrated that the MeAm distribution provides an accurate measure of the pH gradient between the interior and exterior aqueous compartments.…”
Section: Determination Of A*4 and Aphmentioning
confidence: 99%
See 1 more Smart Citation